UJI EFIKASI EKSTRAK DAUN BABADOTAN SEBAGAI INSEKTISIDA NABATI TERHADAP LALAT RUMAH (Musca domestica) DI LABORATORIUM - Dyah Widiastuti; Shinta Shinta (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2008)
A study to evaluate the efficacy of babadotan leaves extract against adult Musca domestica was conducted in Loka Litbang P2B2 Banjarnegara Laboratory at Mei 2008. The study used 5 doses of extract (10,30, 50,70 dan 90%, as well as control treatment). Each doze used 3 replicates. The results showed that babadotan extract was not effective tocontrol more than 70% flies. A nova analysis showed that there was different count of death of flies between control and treated cages.